2019
DOI: 10.1002/jcsm.12490
|View full text |Cite
|
Sign up to set email alerts
|

Defining barriers to implementation of nutritional advice in patients with cachexia

Abstract: Background Cancer cachexia is a multidimensional wasting syndrome and a reduced dietary intake is both common and strongly correlated with degree of weight loss. Many patients with cachexia do not achieve recommended dietary intake even after nutritional counselling. Prior reports suggest this is likely due to barrier symptoms, but other potential contributory factors have not been studied in detail. Methods Dietitian‐assigned barriers to successful nutritional intervention were recorded at each visit in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
See 1 more Smart Citation
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…Articles also explored the associations of protein intake, 46,47 iron deficiency, 37,42 micronutrients, 35 calorie restriction, 43 nitrate dietary intake, 36 retrospective evaluation of early dietary supplementation, 44 and overall dietary intake and patterns 34 with several clinical outcomes and/or biomarkers of sarcopenia or cachexia. Two studies evaluated the perceptions of oncology patients regarding disease‐related nutritional issues and barriers to effective nutritional interventions 45,48 . One narrative review discussed potential nutrition interventions to augment muscle mass 6 …”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“…This primarily can be cultivated by the healthcare professionals and in the event that is poorly addressed then this results to a corresponding behavior by cancer patients and their informal caregivers. Studies show that this can be an attributing factor to poor adherence to nutritional advice ( Nasrah et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The identification, treatment, and regular reviews of malnourished patients and/or those at risk have been shown to confer benefits, such as improved nutrition status and quality of life, regardless of funding availability 16,17 . The additional financial support provided to patients will likely improve compliance to MNPs and nutrition advice provided, as financial constraint is a known social barrier to the implementation of nutrition intervention in patients 18 …”
Section: Discussionmentioning
confidence: 99%